2011
DOI: 10.1002/mnfr.201100064
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term adaptation of global transcription and metabolism in the liver of high‐fat diet‐fed C57BL/6J mice

Abstract: Global transcriptional and metabolic profiling across multiple time points in liver revealed potential targets for nutritional interventions to reverse DIO. In future, new approaches targeting HFD responsive genes and hepatic metabolism could help ameliorate the deleterious effects of an HFD and DIO-related complication.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
80
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 76 publications
(98 citation statements)
references
References 57 publications
17
80
0
1
Order By: Relevance
“…The observed situation may occur due to short period of dietary intervention. In particular, it has been demonstrated that feeding C57BL/6 J mice with a diet consisting of 20 % fat and 1 % cholesterol induces significant changes in serum glucose, insulin, and HOMA-IR values only after 16 weeks [30]. At the same time, significant diet-induced alteration of serum TC and LDL-C was detected after 6 weeks of dietary intervention [30].…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…The observed situation may occur due to short period of dietary intervention. In particular, it has been demonstrated that feeding C57BL/6 J mice with a diet consisting of 20 % fat and 1 % cholesterol induces significant changes in serum glucose, insulin, and HOMA-IR values only after 16 weeks [30]. At the same time, significant diet-induced alteration of serum TC and LDL-C was detected after 6 weeks of dietary intervention [30].…”
Section: Discussionmentioning
confidence: 95%
“…In particular, it has been demonstrated that feeding C57BL/6 J mice with a diet consisting of 20 % fat and 1 % cholesterol induces significant changes in serum glucose, insulin, and HOMA-IR values only after 16 weeks [30]. At the same time, significant diet-induced alteration of serum TC and LDL-C was detected after 6 weeks of dietary intervention [30]. Moreover, feeding of weanling male Sprague-Dawley with a high-fat diet containing 45 % of kilocalorie from fat did not result in a significant change in blood glucose levels after 4, 8, or 12 weeks [31].…”
Section: Discussionmentioning
confidence: 99%
“…Inflammation is a key factor in the progression of fatty liver into more severe stages, and it appears to be required for development of hepatic insulin resistance [33][34][35]. Furthermore, obesity is closely associated with a state of chronic low-grade inflammation [2].…”
Section: Lingonberry and Bilberry Intake Have Antiinflammatory Effectsmentioning
confidence: 99%
“…However, results from anthropometric and biochemical measurements showed that incremental TG was strongly related to an increased risk of NAFLD with the highest ORs, which was consistent with the findings by Fan et al that TG was the most significant predictor (OR: 1.39; 95% CI: 1.25-1.55) in all the blood biochemical indices 9 . The explanation was because, at least in part, excessive accumulation of TG in hepatocytes appeared to be the crucial candidate contributing to hepatic insulin resistance which was dramatically important in the pathogenesis of metabolic syndrome and NAFLD 10,[38][39][40][41] .…”
Section: Discussionmentioning
confidence: 99%